Women’s Drive for Power: Women and Cars in Selected Works of F. Scott Fitzgerald (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper examines the relation between female characters and cars in three F. Scott Fitzgerald's novels:The Great Gatsby, Tender is the Night and The Beautiful and Damned. The introduction offers a brief explanation of the role of stereotyping and generalisation, while the analytical part of the paper examines a concrete stereotype that depicts women as bad drivers, and it also draws a parallel between driving a car and handling power and authority. The main part of the paper focuses on illuminating the characterisation of women through the lens of correlation between their driving skills and gender. Female characters at the steering wheel are portrayed as a danger to themselves and everyone else on the road. Their feminine qualities hinder their driving abilities, thus making them incapable of controlling the power the car gives them and, by extension, any type of power.
Keywords: F. Scott Fitzgerald; feminist criticism; American literature; 20th-century literature; women drivers